Hydroxychloroquine retinopathy: an emerging problem. - Latasiewicz, M; Gourier, H; Yusuf, I; Luqmani, R; Sharma, S; Downes, S (Nature Publishing Group, 2017)
Purpose The aim of this case series is to raise awareness of the emerging issue of serious retinal damage caused by the prolonged use of hydroxychloroquine (HCQ) and the importance of adequate and appropriate monitoring of visual function during treatment. Patients and methods This is a small retrospective case series of 3 patients on long-term HCQ who developed serious symptomatic retinal toxicity confirmed on imaging and functional testing. Results All 3 patients were treated with HCQ for over 15 years; two for rheumatoid arthritis (RA), and the third for systemic lupus erythematosus (SLE). All 3 patients had macular involvement varying in severity confirmed with characteristic features on imaging and functional testing (Optical Coherence Tomography (OCT), Autofluorescence (AF) and Humphrey 10-2 visual fields). Conclusion HCQ is widely used to treat autoimmune conditions with a proven survival benefit in patients with SLE. However, longterm use can be associated with irreversible retinal toxicity. These cases highlight that HCQ, like chloroquine, can also cause visual loss in susceptible individuals. Early detection of presymptomatic retinal changes by the introduction of appropriate screening and monitoring is mandatory to limit the extent of irreversible visual loss due to HCQ retinal toxicity.